Identification of Fenton-like active Cu sites by heteroatom modulation of electronic density - Zhou, Xiao; Huang, Gui-Xiang; Chen, Cai; Chen, Wenxing; Liang, Kuang; Qu, Yunteng; Yang, Jia; Wang, Ying; Li, Fengting; Yu, Han-Qing; Wu, Yuen (Proceedings of the National Academy of Sciences - PNAS, 2022)
Developing heterogeneous catalysts with atomically dispersed active sites is vital to boost peroxymonosulfate (PMS) activation for Fenton-like activity, but how to controllably adjust the electronic configuration of metal centers to further improve the activation kinetics still remains a great challenge. Herein, we report a systematic investigation into heteroatom-doped engineering for tuning the electronic structure of Cu-N₄ sites by integrating electron-deficient boron (B) or electron-rich phosphorus (P) heteroatoms into carbon substrate for PMS activation. The electrondepleted Cu-N₄/C-B is found to exhibit the most active oxidation capacity among the prepared Cu-N₄ single-atom catalysts, which is at the top rankings of the Cu-based catalysts and is superior to most of the state-of-the-art heterogeneous Fenton-like catalysts. Conversely, the electron-enriched Cu-N₄/C-P induces a decrease in PMS activation. Both experimental results and theoretical simulations unravel that the long-range interaction with B atoms decreases the electronic density of Cu active sites and down-shifts the d-band center, and thereby optimizes the adsorption energy for PMS activation. This study provides an approach to finely control the electronic structure of Cu-N₄ sites at the atomic level and is expected to guide the design of smart Fenton-like catalysts.